Analisis Percepatan Proyek Dengan Metode Pertukaran Waktu Dan Biaya - Sugeng Sutikno; Endang Setiadi; Sahur AR (Lembaga Pengembangan Kinerja Dosen, 2023)
Problems in construction projects can occur in various ways, the cause is due to increased implementation time and increased implementation costs. This is caused by several factors, namely the influence of weather, lack of manpower, inadequate or disrupted material supply and insufficient equipment used, as well as the owner himself. Work delays can be anticipated by accelerating the implementation and accelerating project completion with good planning. An alternative commonly used to support the acceleration of activities is to increase working hours and labor, so that it affects the total cost of the project. To speed up the duration of the project, you can use the time and cost exchange method by analyzing the relationship between activities and the duration of each activity, then calculating the crashing program for each alternative, namely adding working hours by 4 working hours, adding 25% of the workforce to get the value cost slope, and compressed project duration starting from the lowest cost slope value for activities that are on the critical path. The result is that the addition of labor is more profitable in terms of costs because there is an increase in total costs in a relatively small amount compared to the addition of working hours, while in terms of time the addition of working hours is more time efficient.